Comparisons of characteristics and outcome between abusive head trauma and non-abusive head trauma in a pediatric intensive care unit - Yi-Ching Liu; I-Chen Chen; Hsin-Ling Yin; Yen-Hsien Wu; Shih-Hsing Lo; Wen-Chen Liang; Twei-Shiun Jaw; Zen-Kong Dai; Jong-Hau Hsu (Journal of the Formosan Medical Association, 2023)
Background: Abusive head trauma (AHT) is the leading cause of death in infants with traumatic brain injury (TBI). Early recognition of AHT is important for improving outcomes, but it can be challenging due to its similar presentations with non-abusive head trauma (nAHT). This study aims to compare clinical presentations and outcomes between infants with AHT and nAHT, and to identify the risk factors for poor outcomes of AHT. Methods: We retrospectively analyzed infants of TBI in our pediatric intensive care unit from January 2014 to December 2020. Clinical manifestations and outcomes were compared between patients with AHT and nAHT. Risk factors for poor outcomes in AHT patients were also analyzed. Results: 60 patients were enrolled for this analysis, including 18 of AHT (30%) and 42 of nAHT (70%). Compared with those with nAHT, patients with AHT were more likely to have conscious change, seizures, limb weakness, and respiratory failure, but with a fewer incidence of skull fractures. Additionally, clinical outcomes of AHT patients were worse, with more cases undergoing neurosurgery, higher Pediatric Overall Performance Category score at discharge, and more anti-epileptic drug (AED) use after discharge. For AHT patients, conscious change is an independent risk factor for a composite poor outcome of mortality, ventilator dependence, or AED use (OR = 21.9, P = 0.04) Conclusion: AHT has a worse outcome than nAHT. Conscious change, seizures and limb weaknesses but not skull fractures are more common in AHT. Conscious change is both an early reminder of AHT and a risk factor for its poor outcomes.